Species-specificity of the glutathione reduced form accumulation in the arboreal plants, testing influence of industrial emissions - Syshchykov, Dmitry (Acta Agraria Debreceniensis, 2010)
Conducted are researches of dynamics of glutathione reduced form maintenance in the leaves of arboreal plants which grow in the zones of different level of contamination by industrial emissions of“Red Lead Factory” LTD and ArselorMittal Kryvyi Rig. For comparison, similar  investigations were conducted in the intact Botanic Garden in s.c.t. Sofievka. Findings testify to absence of negative influence of industrial emissions and, thus, the arboretum of botanical garden also can be examined as conditional control. It was stated that it is set a few strategies of active oxygen forms and their metabolites deactivation, appearing in cells under action of environment negative factors. To our opinion, fluctuation of glutathione reduced form maintenance can examine as an index of plants stability, on which investigational species can be distributed on steady and moderato steady.